Assessment for learning strategies: Amharic Language Teachers’ Practice and Challenges in Ethiopia - Hailay Tesfay Gebremariam; Abate Demissie Gedamu (International Journal of Language Education, 2022)
Assessment is the central point of educational progress; it is the assistant to teachers during and after teaching and learning. One of the assessment genres, assessment for learning is referred to gathering information during teaching and learning, to determine students’ success in learning. The study aims to determine the understanding of assessment for learning strategies and challenges may face in Amharic language teachers.  The participants selected from all levels of general education (1-12 grades), through cluster random sampling, were 180 Amharic language teachers for a questionnaire survey. In addition, twelve (12) teachers and four (4) teachers were selected through cluster random sampling respectively for an interview and informal conversation. The data acquired through the closed-ended questionnaire was analyzed by a one-sample t-test, while the data obtained through an open-ended questionnaire; interviews and informal conversations were analyzed in qualitative verbal description. The results are presented in two ways; the data from the close-ended questionnaire shows that Amharic language teachers are practice assessment for learning strategies in the classrooms, which is statistically significant (P < 0.01). On the other hand, the data from the open-ended questionnaire shows most Amharic language teachers’ reliance is on the old form of assessment and their awareness assessment for learning strategies is limited. In addition, the challenges, based on the practice of assessment for learning strategies in faced in the language classrooms; lack of transparency, lack of knowledge and experience, school administrative problems, lack of training, and reliance on assessment preference are faced. Based on the findings, the study concludes with recommendations that can be implemented to develop assessment for learning strategies in the language classrooms; to minimize the challenges faced by Amharic language teachers in Ethiopian general education (1-12) schools.